Crack Detection Of Beam Using Image Processing (International Journal of Environmental Sciences, 2025)
The earliest sign of structure degrading is a crack in the surface of the concrete. This is important for maintenance because of the concrete and further exposure would seriously harm the environment. The preferred technique for crack determination is manual inspection. In the manual examination, the sketch of the crack is prepared manually, and the conditions of irregularities are noted. While manual inspection has traditionally been the preferred method, it relies heavily on the expertise of specialists and lacks quantitative analysis capabilities. So, Automatic image based crack determination is proposed as replacement. The Proposed system incorporates image processing and data acquisition methodologies for crack detection and assessment of surface degradation for crack detection and assessment of surface degradation. By comparing the proposed method with existing approaches, namely Talab’s and Sattar Dorafshan Method, the accuracy and effectiveness of the proposed approach were evaluated. A dataset comprising 55 images of cracks from a 30-year-old building with a G+3 floor situated in a coastal area was utilized for validation. Images were captured using two different smartphone cameras with resolutions of 64MP and 20MP. The proposed algorithm, implemented in MATLAB R2023a. Results validate the efficiency of the proposed methodology is accurately detecting and assessing cracks, with an accuracy rate of 70% higher than that of the other two methods.